Field evaluation of 3-(N-acetyl-n-butyl) aminopropionic acid ethyl ester - IR3535 as a spatial repellent to control malaria: A Randomised, Before-After-Control-Intervention trial - Joaquim Domingos Lequechane; Luís Filipe Lopes; Luzia Gonçalves; Nicole Azevedo; Ana Paula Abílio; Ana Bernardo Duajá; João Luís Manuel; Henrique Silveira (PLoS ONE, 2026)
Background Malaria remains a major public health challenge in sub-Saharan Africa. Increasing mosquito resistance to insecticides can significantly limit current vector control strategies. Spatial repellents represent a promising complementary tool by disrupting mosquito human-seeking behaviour. This trial aimed to evaluate the efficacy of IR3535 as a spatial repellent in Tambai, a high-transmission rural area in central Mozambique. Methods This was a randomised, Before-After-Control-Intervention trial. Four Tambai blocks were randomly selected, with 40 households randomly assigned to receive IR3535 spraying and 40 assigned to as a no-repellent control group. Plasmodium falciparum malaria prevalence was estimated in children under 5 years of age using polymerase chain reaction, before, at year one and at year two. Data were first analysed using frequentist methods and subsequently using spatiotemporal Bayesian models, incorporating INLA-based models to assess the impact of repellent intervention on mosquito density and diversity, sporozoite rates, and malaria prevalence in the repellent and control groups. Results A total of 5716 mosquitoes were collected, 57.2% were Anopheles and 42.7% were Culex sp. . An. funestus s.l. females, were the most prevalent mosquito both indoor (92.7%) and outdoor (82.5%), followed by An. gambiae and An. tenebrosus . The total number of An. funestus s.l. females was lower in the repellent group compared with the control group [indoors: 765 vs 1,432; outdoors: 175 vs 293], as was the average number of mosquitoes collected per household [indoors: 18.6 vs 35.0; outdoors: 4.3 vs 7.1]. Spatiotemporal analysis revealed evidence of repellent-associated reduction in mosquito densities, with species-specific and indoor-outdoor differences, highlighting An. funestus s.l. dominance and spatial-temporal clustering patterns. P. falciparum prevalence among children under five declined from 72.6% (95% CI = 64.1–80.2) at baseline to 51.3% (95% CI = 43.5–59.1) at year one and 43.3% (95% CI = 35.7–51.1) at the end of the study, with similar reductions in both repellent and control groups. Sporozoite rates were slightly lower in the repellent group, particularly outdoors, however, these differences could not be directedly attributed to the repellent. Conclusion Our findings indicate that the use of IR3535 as a spatial repellent reduces indoor and outdoor malaria vector densities, which may contribute to reduced malaria transmission. Trial registration ClinicalTrials.gov NCT04419766